Reversed Intestinal Rotation Presented as Bowel Obstruction in a Pregnant Woman. (17th May 2015) - Aranovich, David; Schrier, Ilan
Abstract : A rare case of complete large bowel obstruction in a pregnant woman, without previous surgical history, due to previously undiagnosed reversed intestinal rotation is presented. The young woman was admitted with progressive nausea and vomiting which did not respond to conventional therapy. Her plain abdominal film revealed signs of small bowel obstruction. On laparotomy, her transverse colon was found to be located beneath the root of small bowel mesentery and completely obstructed by congenital fibrous bands. Postoperative recovery was unremarkable. Surgery for this unusual developmental anomaly is discussed.